The Role of Professional Commitment in Mediating the Influence of Job Autonomy on Employee Job Engagement - Jack H. Syauta; Elimelek Ramandey; Chrisostommi W. Tuhumena (Westscience Press, 2026)
This study aims to explain the effect of job autonomy on professional commitment, the effect of job autonomy on job engagement, the effect of professional commitment on job engagement, and the mediating role of professional commitment in the effect of job autonomy on the job engagement of employees at the Class II Harbormaster and Port Authority Office (KSOP) of Jayapura. The research employed an explanatory design with a quantitative approach grounded in the Job Demands–Resources model. The population, which also served as the sample, comprised all 67 civil servants, selected through a census (saturated sampling) technique. Data were collected through a 1–5 Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with SmartPLS. The results show that job autonomy has a positive and significant effect on professional commitment (path 0.915; p 0.000); job autonomy has a positive and significant effect on job engagement (path 0.769; p 0.000); professional commitment has a positive and significant effect on job engagement (path 0.231; p 0.000); and job autonomy has a positive and significant effect on job engagement through the mediation of professional commitment (path 0.210; p 0.000), categorized as moderate mediation (upsilon v = 0.0447). The model demonstrates relevant predictive value (Q² = 0.9943). These findings confirm that increasing job autonomy as a job resource should be directed toward strengthening professional commitment in order to enhance employee job engagement.